1995
DOI: 10.1007/bf02128749
|View full text |Cite
|
Sign up to set email alerts
|

Oyster mushroom (Pleurotus ostreatus) reduces the activity of 3-hydroxy-3-methylglutaryl CoA reductase in rat liver microsomes

Abstract: The effect of dried oyster mushroom (Pleurotus ostreatus) on cholesterol (C) content in serum, in lipoproteins and in liver, and on the activity of 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase in liver microsomes, was studied in male rats (strain Wistar, initial body weight 75 g) fed on low-cholesterol (9 mg/100 g) and high-cholesterol (0.3%) diets. Addition of 5% oyster mushroom to both diets reduced significantly the C-content in serum (by 30%), in very-low- and low-density lipoproteins (in a 1:1 ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…In another study, dietary fiber extracted from P. cornucopiae had a marked antiatherosclerotic effect in vitro, and patients with coronary disease showed a decreased atherogenic activity (20-40%) in their sera after the consumption of this mushroom, which confirms that it has a natural cholesterol-lowering agent that is responsible for this hypocholesterolemic effect (Ryong et al, 1989). Addition of 1-5% of oyster mushroom to a hyperlipidemic diet efficiently prevents the accumulation of LDL cholesterol and triacylglyceride in both the blood and liver of rats with hyperlipidemia (Bobek et al, 1998) and also reduces cholesterol biosynthesis by suppressing the activity of hepatic HMG-CoA reductase (Bobek et al, 1995) and accelerated cholesterol catabolism by up-regulating hepatic cholesterol 7β-hydroxylase (Bobek et al, 1994). It has been suggested that the fruiting bodies of oyster mushrooms could be recommended for consumption as a natural cholesterol-lowering agent in the human diet (Cimerman, 1999).…”
Section: Mushrooms As Hypocholesterolemic Agentsmentioning
confidence: 66%
“…In another study, dietary fiber extracted from P. cornucopiae had a marked antiatherosclerotic effect in vitro, and patients with coronary disease showed a decreased atherogenic activity (20-40%) in their sera after the consumption of this mushroom, which confirms that it has a natural cholesterol-lowering agent that is responsible for this hypocholesterolemic effect (Ryong et al, 1989). Addition of 1-5% of oyster mushroom to a hyperlipidemic diet efficiently prevents the accumulation of LDL cholesterol and triacylglyceride in both the blood and liver of rats with hyperlipidemia (Bobek et al, 1998) and also reduces cholesterol biosynthesis by suppressing the activity of hepatic HMG-CoA reductase (Bobek et al, 1995) and accelerated cholesterol catabolism by up-regulating hepatic cholesterol 7β-hydroxylase (Bobek et al, 1994). It has been suggested that the fruiting bodies of oyster mushrooms could be recommended for consumption as a natural cholesterol-lowering agent in the human diet (Cimerman, 1999).…”
Section: Mushrooms As Hypocholesterolemic Agentsmentioning
confidence: 66%
“…A substantial reduction of total cholesterol in serum by PM-F2-OB could be attributed to a reduction in the activities of the liver enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase, which is a rate-limiting enzyme in cholesterol biosynthesis. 42) Also, a substantial reduction in Fig, 3. Protective Effect of PM-F2-OM on Liver…”
Section: Discussionmentioning
confidence: 94%
“…This could be due to a reduction in the activity of the liver enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase. 15) Therefore it is suggested that the hypocholesterolemic effect of HW extract from cultured mycelia of C. sinensis might be mediated by several mechanisms. A substantial reduction in LDL cholesterol and TC levels in serum could also be achieved by reduced production of TC by liver tissue and/or efficient removal of the LDL cholesterol by various tissues without subsequent renewal.…”
Section: Mycelial Growth In the Jar Fermentermentioning
confidence: 99%